Fiberoptic Endoscopic Evaluation of Swallowing (FEES) with and without Blue-Dyed Food - Leder, Steven B.; Acton, Lynn M.; Lisitano, Heather L.; Murray, Joseph T. (Dysphagia, 2005)
The purpose of this prospective study was to determine if fiberoptic endoscopic evaluation of swallowing (FEES) maintains high intra- and interrater reliability in detecting pharyngeal dysphagia and aspiration without the addition of FD&C Blue No. 1 to food. Twenty consecutive adults referred for a swallow evaluation participated. Nine subjects received blue-dyed food and 11 subjects received regular nondyed food, i.e., yellow pudding and white skim milk. Four variables were rated: (1) the stage transition characterized by depth of bolus flow to at least the vallecula prior to the pharyngeal swallow; (2) evidence of bolus retention in the vallecula or pyriform sinuses after the pharyngeal swallow; (3) laryngeal penetration defined as material in the laryngeal vestibule but not passing below the level of the true vocal folds either before or after the pharyngeal swallow; and (4) tracheal aspiration defined as material below the level of the true vocal folds either before or after the pharyngeal swallow. Three speech–language pathologists experienced in interpreting FEES results independently and blindly reviewed the digitized videotape three times. Intrarater agreements for the four variables with blue-dyed and non-blue-dyed food trials were 100% and monochrome trials ranged from 95% to 100%. Average kappa values for interrater reliability ranged from moderate to excellent agreement (0.61–1.00) for all viewing conditions. Kappa values for blue-dyed trials versus monochrome trials were 0.83 and for non-blue-dyed trials versus monochrome trials were 0.88, indicative of excellent reliability under both viewing conditions. FEES maintains both high intra- and interrater reliability in detecting the critical features of pharyngeal dysphagia and aspiration using either blue-dyed or non-blue-dyed foods. The endoscopist, therefore, can be assured of reliable FEES results using regular, non-dyed food trials.
Keywords: Aspiration; Blue dye; Deglutition; Deglutition disorders; Fiberoptic endoscopic evaluation of swallowing; Pharyngeal dysphagia; dept.cmd; peer-reviewed

Evidence-based practice among speech-language pathologists: attitudes, utilization, and barriers. - Zipoli, Richard P Jr; Kennedy, Marianne (American Journal of Speech-language Pathology, 2005)
A total of 240 speech-language pathologists responded to a questionnaire examining attitudes toward and use of research and evidence-based practice (EBP). Perceived barriers to EBP were also explored. Positive attitudes toward research and EBP were reported. Attitudes were predicted by exposure to research and EBP practice during graduate training and the clinical fellowship year (CFY). Clinical experience and opinions of colleagues were used to guide decision making more frequently than research studies or clinical practice guidelines. Only exposure to research and EBP during the CFY predicted use of evidence-based resources. Respondents reported a decline in exposure to research and EBP as they moved from graduate training into the CFY. A lack of time was perceived as a barrier to EBP.
Keywords: *Attitude of Health Personnel; *Data Collection/sn [Statistics & Numerical Data]; *Evidence-Based Medicine; *Health Knowledge, Attitudes, Practice; *Speech-Language Pathology/st [Standards]; Clinical fellowship; Evidence-based practice; Humans; Practice issues; Research; Speech-Language Pathology/sn [Statistics & Numerical Data]; Speech-language pathology; Surveys and Questionnaires; United States; dept.cmd

Educating and training caregivers of persons with aphasia - Purdy, Mary; Hindenlang, Jane (Aphasiology, 2005)
Background: Because communication deficits caused by aphasia affect both persons with aphasia and their communication partners, most speech-language pathologists are aware of the importance of client and caregiver education. To maximise the effectiveness of their communicative interactions, training should be conducted for both the aphasic clients and their caregivers. Training conducted in group environments offers peer support through shared learning experiences and joint problem solving. Aims: The purpose of this study was to explore the benefits of a caregiver education and training programme in improving communication between caregivers and their aphasic partners using didactic and experiential approaches in a group setting. Methods & procedures: Ten caregivers and their aphasic partners, ranging from 4 to 130 months post-stroke, participated in a 12-week group training and education programme. Information about stroke and aphasia was provided in a didactic format, and facilitative communication strategies were discussed and practised using Kolb's (1984) experiential learning cycle model. The experiential learning cycle involved drawing on concrete experiences, engaging in reflective observation and abstract conceptualisation, and practising what was learned through active experimentation. Outcomes & results: Analysis of communicative performance on transactional and interactional tasks demonstrated increased communicative success. Responses on a questionnaire indicated that participants had a better understanding of aphasia and were more confident using facilitating strategies. Conclusions: Group education and training for caregivers and their aphasic partners can be beneficial, even after the couple has been living with aphasia for a number of years. Having an opportunity to practise, observe, and reflect on their performances facilitated participants' learning, and there were observed and reported positive alterations in interactions. © 2005 Psychology Press Ltd.
Keywords: adult; aged; aphasia; article; caregiver; cerebrovascular accident; clinical article; cognition; dept.cmd; disease severity; education program; experience; female; group therapy; health education; human; information dissemination; interpersonal communication; learning; male; medical education; patient education; peer-reviewed; problem solving; questionnaire; self concept; social support; task performance

Perception and Production of Prosody by Speakers with Autism Spectrum Disorders. - Paul, Rhea; Augustyn, Amy; Klin, Ami; Volkmar, Fred R (Journal of Autism and Developmental Disorders, 2005)
Speakers with autism spectrum disorders (ASD) show difficulties in suprasegmental aspects of speech production, or prosody, those aspects of speech that accompany words and sentences and create what is commonly called "tone of voice." However, little is known about the perception of prosody, or about the specific aspects of prosodic production that result in the perception of "oddness." The present study examined the perception and production of a range of specific prosodic elements in an experimental protocol involving natural speech among speakers with ASD between 14 and 21 years of age, in comparison with a typical control group. Results revealed ceiling effects limiting interpretation of findings for some aspects of prosody. However, there were significant between-group differences in aspects of stress perception and production. The implications of these findings for understanding prosodic deficits is speakers with autism spectrum disorders, and for future research in this area, are discussed.
Keywords: *Autistic Disorder/co [Complications]; *Language Disorders/et [Etiology]; *Perceptual Disorders/et [Etiology]; *Phonetics; *Speech Disorders/et [Etiology]; *Speech Perception; Adolescent; Adult; Autism; Autistic Disorder; Humans; Language; Language Disorders; Language Disorders/di [Diagnosis]; Language Tests; Male; Perceptual Disorders; Perceptual Disorders/di [Diagnosis]; Phonetics; Prosody; Speech Discrimination Tests; Speech Disorders; Speech Disorders/di [Diagnosis]; Speech Perception; Speech Production Measurement; article; autism; child; clinical article; clinical protocol; controlled study; correlation analysis; dept.cmd; human; intelligence quotient; intermethod comparison; language; medical assessment; peer-reviewed; perception; priority journal; prosody; reliability; scoring system; speech; speech disorder; statistical significance; stress; task performance

Communication quality indicators: A survey of connecticut group home managers - Desimone, Evelyn A; Cascella, Paul W (Journal of Developmental and Physical Disabilities, 2005)
Thirty-one Connecticut group home managers responded to a 23-statement survey adapted from the Communications Supports Checklist for Programs Serving Individuals with Severe Disabilities (CSC; McCarthy et al., 1998, Paul H. Brookes, Baltimore, MD.). Results indicated that group home managers had very favorable opinions about the implementation of communication quality indicators in their group homes, and the degree of a resident's intellectual disability was not a factor in communication supports implementation. Three communication quality indicators were rated especially high: program philosophy, protection of communication rights, and assessment. Environmental support for communication was rated less favorably. Follow-up interviews with seven group home managers found that they especially valued direct care staff who understood a resident's idiosyncratic communication (e.g., response sensitivity). Managers also relied on team process for referral for ongoing speech-language consultation. Results from the surveys and interviews indicated that augmentative communication applications occurred less often than other quality communication indicators.
Keywords: Communication supports; Group home; Severe disabilities; dept.cmd; peer-reviewed

Gin (gaps-in-noise) test performance in subjects with confirmed central auditory nervous system involvement - Musiek, Frank E; Shinn, Jennifer B; Jirsa, Robert E; Bamiou, Doriseva; Baran, Jane A; Zaida, Elena (Ear and Hearing, 2005)
OBJECTIVE: The purpose of the present study was to investigate the value of a new gap detection procedure called Gaps-In-Noise (GIN) for assessment of temporal resolution in a clinical population. DESIGN: The test consists of 0 to 3 silent intervals ranging from 2 to 20 msec embedded in 6-sec segments of white noise. The location, number, and duration of the gaps per noise segment vary throughout the test for a total of 60 gaps presented in each of four lists. The GIN procedure was administered to 50 normal-hearing listeners (group I) and 18 subjects with confirmed neurological involvement of the central auditory nervous system (group II). RESULTS: Results showed mean approximated gap detection thresholds of 4.8 msec for the left ear and 4.9 msec for the right ear for group I. In comparison, results for group II demonstrated a statistically significant increase in gap detection thresholds, with approximated thresholds of 7.8 msec and 8.5 msec being noted for the left and right ears, respectively. Significant mean differences were also observed in the overall performance scores (i.e., the identification of the presence of the gaps within the noise segments) of the two groups of subjects. Finally, psychometric functions, although similar for short and long duration gaps, were highly different for gaps in the 4- to 10-msec range for the two groups. CONCLUSIONS: A variety of psychoacoustic procedures are available to assess temporal resolution; however, the clinical use of these procedures is minimal at best. Results of the present study show that the GIN test holds promise as a clinically useful tool in the assessment of temporal resolution in the clinical arena. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Adolescent; Adult; Aged; Aneurysm; Auditory Diseases, Central; Auditory Threshold; Case-Control Studies; Cerebrovascular Accident; Electrophysiology; Evoked Potentials, Auditory; Female; Humans; Male; Middle Aged; Noise; Perceptual Masking; Reaction Time; Reproducibility of Results; Stroke; adolescent; adrenoleukodystrophy; adult; article; auditory nervous system; brain artery aneurysm; clinical article; controlled study; dept.cmd; false positive result; female; gaps in noise test; hearing; hemispheric dominance; human; learning disorder; male; noise; pitch; psychometry; psychophysics; pure tone audiometry; receiver operating characteristic; stroke; temporal summation; test retest reliability; white noise

Brief Report: Relations between Prosodic Performance and Communication and Socialization Ratings in High Functioning Speakers with Autism Spectrum Disorders. - Paul, Rhea; Shriberg, Lawrence; McSweeny, Jane; Cicchetti, Domenic; Klin, Ami; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2005)
Shriberg et al. [ Shriberg, L. et al. (2001). Journal of Speech, Language and Hearing Research, 44, 1097-1115] described prosody-voice features of 30 high functioning speakers with autistic spectrum disorder (ASD) compared to age-matched control speakers. The present study reports additional information on the speakers with ASD, including associations among prosody-voice variables and ratings of communication social abilities. Results suggest that the inappropriate sentential stress and hypernasality previously identified in some of these speakers is related to communication/sociability ratings. These findings and associated trends are interpreted to indicate important links between prosodic performance and social and communicative competence. They suggest the need for careful assessment of inappropriate prosody and voice features in speakers with ASD, and for effective intervention programs aimed at reducing the stigmatization of individuals with these conditions., (C) Plenum Publishing Corporation 2005. All Rights Reserved.
Keywords: Adolescent; Adult; Asperger syndrome; Autism; Autistic Disorder; Communication; Female; Humans; Male; Middle Aged; Prosody; Severity of Illness Index; Socialization; Speech; Speech Production Measurement; Voice Quality; adolescent; adult; article; autism; child; clinical article; communication; communication skill; controlled study; dept.cmd; female; hospitalization; human; human experiment; interpersonal communication; linguistics; male; middle aged; nasal speech; peer-reviewed; priority journal; prosody; social adaptation; social psychology; socialization; speech; speech analysis; speech disorder; verbal communication; voice